Números irracionais e suas particularidades - Garcia, Hévila Maria Gabriel (Universidade Federal de São Carlos, 2022)
In this work we present the main numerical sets: natural, integers, rational, irrational and real, focusing on the set of irrational numbers. We approach its historical part, the most famous examples and the proof of their irrationalities. In addition, we deal with the concepts of transcendental and algebraic numbers. In the second part, we discuss the way that the set of irrational numbers is approached in Basic Education and, moreover, we create and apply an activity involving the numerical sets in a State School.
Irrational numbers and their characteristics
Keywords: Números irracionais; Irracionalidade; História dos números irracionais; Avaliação diagnóstica; Irracionais na Educação Básica; Irrational numbers; Irrationality; History of irrational numbers; Diagnostic evaluation; Irrationals in the Elementary School; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ANALISE